Companions' Chronicles: Experiences of Home Care Workers in the Community Elder Care (Companion) Program in Barbados. (April 2023) - Odle-James, Thérèse; Willie-Tyndale, Douladel
The home care workforce contributes significantly to older adults' health and well-being. The Community Elder Care (Companion) Program in Barbados employs Companions to engage with socially isolated older adults in their homes for a few hours per day. In this qualitative study we explored Companions' experiences in the program 1 year since its commencement. Opportunity to earn, love and concern for older adults, and previous caregiving experiences were among the factors which motivated participants to seek employment in the program. They commonly reported going beyond the scope of their duties to meet clients' critical needs. While they saw themselves as positively impacting their clients, some noted that they too benefitted from the engagement. Better compensation packages and training were seen as necessary actions for program improvement. Our findings can be incorporated in a comprehensive program review and can inform home care workforce development and Companion Program structure and delivery.